Bending Properties of Wood Flour Filled Polyethylene in Wet Environment. (2017) - Mazzanti, V.; Mollica, F.
Abstract: Wood polymer composites (WPCs) are made of a mixture of a thermoplastic or thermoset polymer, wood fiber or sawdust and small amount of additives. These materials represent an increasingly growing area in polymer industry, in particular they are frequently used as substitutes of wood especially for outdoor products in wet environment. This particular application is due to the hydrophobicity of the matrix that protects the natural fiber reinforcement and increases the durability of the final product. The present work investigates the bending properties and the water uptake of wood flour filled polyethylene in a range of temperatures, spanning from 10°C up to 40°C. The tests show a remarkable decrease of the mechanical properties, in particular strength and stiffness, and an increase in ductility with increasing water temperature. The water uptake tests have shown the influence of temperature on the characteristics of diffusion.